Antibiosis activities against burkholderia pseudomallei by other burkholderia species - Nur Ezzah, binti Sainei (Universiti Malaysia Sarawak (UNIMAS), 2015)
Burkholderia pseudomallei is known as a significant causative agent of melioidosis and a versatile species of bacteria which inhabit diverse ecological niches including soil and water sources. By studying and understanding the nature of antibiosis activities against B. pseudomallei by other antagonistic Burkholderia species, Burkholderia spp. that are potentially capable of inhibiting the growth of B. pseudomallei are determined to serve as possible biocontrol for the widespread of melioidosis. In this study, certain Burkholderia spp. such as Burkholderia cepacia-complex and Burkholderia ubonensis displayed strong inhibition against B. pseudomallei. Bacteriocins in a cell free state (CFS) isolated from Burkholderia spp. were found to inhibit B. pseudomallei as well. Further characterization of the bacteriocins through various heat treatments indicated that the stability of bacteriocins to heat treatments varies greatly depending on strain-type and exposure to alkaline conditions substantially enhanced the inhibitory activities of the bacteriocins. Subjection to trypsin digestion and freezing showed that the bacteriocins contained both protease-sensitive and phage-like compounds.